Development, implementation and evaluation of nutrition guidelines on the dietary behaviour of the elderly in Ondo City, Nigeria - Olomo, Jerome Abiola (Vaal University of Technology, 2021)
The elderly in Nigeria are used to consuming foods that are inadequate in providing the required amount of nutrients for a healthy living due to uninformed food choices and dietary food intake habits. The main objective of this study was to determine the impact of the developed food and nutrition guidelines on the dietary behaviour of the elderly in Ondo West city Ondo, Nigeria. The developed food and nutrition guidelines were used to generate a training manual for the caregivers’ in order to apply and disseminate the correct information about food nutrients and food choices to the elderly through the knowledge acquired in the nutrition education training programme by the caregivers. A baseline study was conducted making use of the measuring instruments namely, socio-demographic questionnaire, 24-hour recall, food frequency questionnaire completed by the elderly attending the old people’s home and a nutrition knowledge questionnaire to test the nutrition knowledge of the caregivers. The methodology for the study was in six phases: Phase 1: is about the baseline survey, involving the training of fieldworkers, administering and completing questionnaires: Socio-demographic, 24-hour recall, food frequency questionnaire (FFQ), by the elderly and the nutrition knowledge questionnaire (NKQ) by the caregivers. Phase 2: It involved the planning and development of food and nutrition guidelines for the caregivers of the elderly. Phase 3: This phase is about the training of the caregivers by the researcher, making use of the developed training manual with information sourced from the developed food and nutrition guidelines. Phase 4 was about the intervention programme in the study, i.e. the nutrition education programme (NEP) using information from guidelines of USA, Europe, New Zealand, South Africa, Nigeria and adapted FAO framework. Phase 5 was about the evaluation of the study, involving the completion of the nutrition knowledge questionnaire (NKQ), by the caregivers on post-test assessment after intervention, conducting observation and group interview. Phase 6 involved determining the impact of the food and nutrition guidelines and conducting a post-test making use of the research instruments, 24-hour recall, and food frequency questionnaires (FFQ) with the main objective drawn and followed up by the conclusion and recommendations in the study. A content analysis of both the observation and focus group discussion resulted in compliance with the food and nutrition guideline specifications and a remarkable improvement on food preparation skills and performance of the old people’s homes’ personnel. The main findings in the study revealed that consistent and, full compliance, with effective implementation of the food and nutrition guidelines would improve the older people’s dietary behaviour and food consumption patterns. The NEP did not improve the knowledge of the caregivers at the expected rate and level because of the low-level basic scientific background of the caregivers. The socio-demographic questionnaire revealed that 61.7% of those researched were females and 38.3% males with an average age between 60 and 65 years; 54% were married with a household income between N20001- N50000 and majority of them spending between N10001-N15000 on two meals (40%) and three meals (30%). The result from 24-hour recall and the food frequency (FFQ) questionnaires indicated that, the intake of energy, calcium and fiber were below the recommended daily allowance (RDA), while protein and carbohydrate were higher, with an emphasis on starchy foods. The nutrition knowledge questionnaire (NKQ) identified the need for higher level of food and nutrients by the caregivers in their responsibility to the elderly, for improvement in their healthy dietary habits as indicated in the four sections of NKQ results (A, B, C and D). The consumption of fruits and vegetables were impressively high, after the intervention compared to before. Moreover, there was a drastic reduction in the consumption of carbohydrate-sourced food items, fat, sugar and salt as informed by the developed guidelines. Conclusively, the study was able to establish a reliable basis on the improvement of nutrient based dietary intake with the effective utilisation of available information in the guidelines. Also, awareness was created for the elderly to improve their eating habits through the exposure of the caregivers to training on nutrition knowledge. The researcher recommended an in-house organized refresher programme which should take place periodically and consistently on the information in the developed nutrition guidelines along with encouraging the personnel in the handling of foods (caregivers, chefs, cooks) for effective implementation.
D. Tech. (Department of Tourism and Hospitality Management, Faculty of Human Sciences) Vaal University of Technology.
Keywords: Food and nutrition guidelines; Elderly; Caregivers; Dietary intake behaviour; Old people’s homes; Dissertations, Academic -- South Africa; Older people -- Nutrition -- Nigeria -- Ondo City -- Evaluation; Caregivers -- Service for